2021
DOI: 10.1101/2021.09.02.458777
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alterations in gut microbiome composition and function in irritable bowel syndrome and increased probiotic abundance with daily supplementation

Abstract: Background. Irritable bowel syndrome (IBS) is characterized by abdominal discomfort and irregular bowel movements and stool consistency. Because there are different symptoms associated with IBS, it is difficult to diagnose the role of the microbiome in IBS. Objective. Here, we present a study that includes metagenomic sequencing of stool samples from subjects with the predominant subtypes of IBS and a healthy cohort. We collected longitudinal samples from individuals with IBS who took daily made-to-order preci… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 99 publications
(109 reference statements)
1
2
0
Order By: Relevance
“…including A. odontolyticus as seen here [7]. Additional species level microbial shifts detected by 16S sequencing or metatranscriptomics that have been previously noted in large shotgun metagenomics studies include increased Streptococcus species (S. parasanguinis), Eggerthella lenta, and Blautia hydrogenotrophica as well as reduced Faecalibacterium prausnitzii, Bacteroides thetaiotaomicron, and Bilophila wadsworthia [11,16,23]. Other taxonomic shifts observed in this study have not been previously reported and many taxa that were reported in prior studies were not significant in our study.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…including A. odontolyticus as seen here [7]. Additional species level microbial shifts detected by 16S sequencing or metatranscriptomics that have been previously noted in large shotgun metagenomics studies include increased Streptococcus species (S. parasanguinis), Eggerthella lenta, and Blautia hydrogenotrophica as well as reduced Faecalibacterium prausnitzii, Bacteroides thetaiotaomicron, and Bilophila wadsworthia [11,16,23]. Other taxonomic shifts observed in this study have not been previously reported and many taxa that were reported in prior studies were not significant in our study.…”
Section: Discussionsupporting
confidence: 64%
“…These differences could reflect multiple factors that differentiated our study including racial/ethnic composition, recruitment of subjects from the community rather than specialty clinics, and differences in analytical approach. Importantly, this study differed from many prior ones in using multivariate strategies to adjust for a wide range of covariates differing between IBS and HC that could confound analyses [7,11,[13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation